2017
DOI: 10.1038/cddis.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of reactive oxygen species (ROS) for synergistic enhancement of apoptosis by vemurafenib and the potassium channel inhibitor TRAM-34 in melanoma cells

Abstract: Inhibition of MAP kinase pathways by selective BRAF inhibitors, such as vemurafenib and dabrafenib, have evolved as key therapies of BRAF-mutated melanoma. However, tumor relapse and therapy resistance have remained as major problems, which may be addressed by combination with other pathway inhibitors. Here we identified the potassium channel inhibitor TRAM-34 as highly effective in combination with vemurafenib. Thus apoptosis was significantly enhanced and cell viability was decreased. The combination vemuraf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…Our data showed that the viability of A375 and B16-F10 melanoma cells were not allergic to ORI's treatment compared with other cancer cell lines (47,48). As the literature reported that ROS represents an initial and independent apoptosis pathway in melanoma cells (49). So we speculate that ORI can not trigger the ROS system inducing the apoptosis pathway in melanoma cells at lower concentrations (5 and 10 µM).…”
Section: Discussionmentioning
confidence: 55%
“…Our data showed that the viability of A375 and B16-F10 melanoma cells were not allergic to ORI's treatment compared with other cancer cell lines (47,48). As the literature reported that ROS represents an initial and independent apoptosis pathway in melanoma cells (49). So we speculate that ORI can not trigger the ROS system inducing the apoptosis pathway in melanoma cells at lower concentrations (5 and 10 µM).…”
Section: Discussionmentioning
confidence: 55%
“…For ROS generation by DKP‐073, NOX enzymes may be involved as suggested by two used NOX inhibitors. The critical role of ROS in apoptosis regulation in melanoma cells was also seen, when other therapeutic strategies were applied, as chemotherapy and radiotherapy, elesclomol, PI3K inhibition, or BRAF inhibition …”
Section: Discussionmentioning
confidence: 94%
“…However, its relation to other described apoptosis pathways remained fragmentary so far. In melanoma cells, we have previously described enhanced ROS levels in response to inhibition of phospoinositol‐3 kinase (PI3K) as well as to inhibition of BRAF …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that mitochondria serve a crucial function in the extrinsic and intrinsic pathways of apoptosis; the structural integrity and normal function of mitochondrial membranes are critical for cell survival (22). Notably, if the structure and function of mitochondrial membranes sustain damage, for example through ultraviolet irradiation, genotoxic agents or oxidative stress, this will trigger a series of cellular events that will affect the basic characteristics of malignant tumors, such as the proliferation, invasion and metastasis, and even induce cells apoptosis or necrosis (23).…”
Section: Discussionmentioning
confidence: 99%